Creep behavior of a solder paste with BI addition - Ribeiro, Pedro Emanuel Abreu (2018)
A common failure mode of electronic PCB’s is the appearance of cold solder joints between the component and PCB, during product life. This phenomenon is related to solder joint fatigue and is attributed mainly to the mismatch of the coefficients of thermal expansion (CTE) of component-solder-PCB assembly. Although some experiments show that newer lead-free tin-silver-copper (Sn-Ag-Cu, or SAC) solders perform better than the older SnPb ones, with today’s solder joint thickness decreasing and increasing working temperatures, among others, the stresses and strains due to temperature changes are growing, leading to limited fatigue life of the products. As fatigue life decreases with increasing plastic strain, creep occurrence should have significant impact, especially during thermal cycles. In order to improve mechanical properties, but also as an attempt to reduce maximum reflow cycle temperatures due to component damage and production costs, various SAC solder alloying additives are being considered to use in industrial production facilities. Solder paste producers are proposing new products based on new solder paste formulations, but the real life effects on thermo-mechanical performance aren’t well known at the moment. In this paper a dynamic mechanical analyser (DMA) is used to study the influence of Bismuth (Bi) addition, up to 5 wt %, on SAC405 solder paste, in terms of creep behaviour. Creep tests were made on three-point-bending configuration, isothermally at 30 ºC, 50 ºC and 75 ºC, and three different stresses of 3, 5 and 9 MPa. The results shown not only a significant Bi concentration influence on creep behaviour but also a noticeable temperature dependence.